Standardization of pre-sowing seed treatment with selected botanicals on growth, yield and yield attributing traits of linseed (Linum usitatissimum L.): STANDARDIZATION OF PRE-SOWING SEED TREATMENT WITH SELECTED BOTANICALS OF LINSEED - MATTAPELLY DIVYA; PRASHANT KUMAR RAI (Journal of Oilseeds Research, 2024)
The present study was aimed to determine the effect of different doses and duration of pongamia, tulsi, moringa and neem leaf extract on growth, yield and yield attributing traits of linseed (cv. GP-I-44). A field study was conducted during rabi 2022-2023 at the field experimentation centre of Department of Genetics and Plant breeding, Sam Higginbottom University of Agriculture Technology and Sciences, Prayagraj. The study was carried out in a Randomized Block Design with 13 treatment combinations in three replications to assess the effect of seed priming with botanicals on linseed seeds under various levels of pongamia leaf extract, tulsi leaf extract, moringa leaf extract and neem leaf extract. The highest recorded yield attributes were observed in T3, where pongamia leaf extract at a concentration of 10% resulted in 114.33 capsules/plant, 8.77 seeds/capsule, 4.5 g/plant, 73.37 g/plot, and 733 kg/ha, with a 1000-seed weight of 8.15 g. Conversely, the lowest values were recorded in T7, with moringa leaf extract at 3% resulting in 105.00 capsules/plant, 7.67 seeds/capsule, 2.4 g/plant, 67.13 g/plot, and 671 kg/ha, with a 1000-seed weight of 7.15 g. Thus, the application of pongamia leaf extract at 10% concentration (T3) emerged as the most effective dosage for priming linseed.